Optimizing Religious Moderation through Progressive Islamic Education: A Philosophical Study - Uswatun Hasanah; Asghar Abbas (Kopertais Wilayah XV Lampung, 2023)
Islamic education has an essential role in shaping religious moderation. However, the increasingly complex challenges of extremism and religious intolerance require a more progressive approach to dealing with them. This research aims to optimize religious moderation through progressive Islamic education and examine the philosophy of Islamic education as a conceptual foundation. This study used a qualitative approach with literature analysis and documentation data collection techniques. The research results show the importance of religious moderation in complex social, political, and cultural contexts. The philosophy of Islamic education provides a solid theoretical and methodological foundation for developing a progressive Islamic education that promotes religious moderation. Ontologically, the understanding of religious moderation emphasizes recognition of the complexity of spiritual reality and the importance of tolerance for different interpretations and practices. In epistemology, a moderate approach recognizes that knowledge about religion is limited and influenced by social and cultural factors. Therefore, critical thinking, interreligious dialogue, and continuous learning are essential in achieving religious moderation. In axiology, religious moderation emphasizes values such as tolerance, mutual respect, peace, justice, and the adaptability of values to the development of society and changing times. In conclusion, optimizing religious moderation through progressive Islamic education based on a study of Islamic educational philosophy encourages a broader understanding and application of religious moderation in society, especially in the context of diverse, multicultural education.